THE RELATIONSHIP OF THE LENGTH OF DAY OF STAYING WITH THE LEVEL OF ANXIETY OF THE PATIENT'S FAMILY IN THE ROOM INTENSIVE CARE UNIT (LITERATURE REVIEW) - Ananda, Riandika; Azizah , Aisyah Nur (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: The Intensive Care Unit (ICU) is a unit in a hospital that functions to care for critical patients. The condition of the patient being treated in the intensive care unit will affect the length of the patient's treatment period. In this situation, it will be possible for the family to feel anxious because family members are experiencing critical care and experiencing challenges which are anxiety factors due to being treated in the intensive care unit. Objective: The aim of this research is to determine the relationship between the length of hospital stay and the anxiety level of the patient's family in the intensive care unit through literature. Research Method: This research is a literature review with journals obtained from Google Scholar and PubMed published in 2019-2024. Results: Research based on literature review analysis can be concluded as follows: Length of stay based on journal analysis states that the average length of stay for patients is at the level of the long stay category. The results of anxiety measurements based on journal analysis show that the average patient's family anxiety is moderate anxiety. Based on the literature review analysis, it can be concluded that there is a relationship between the length of a patient's stay and the anxiety level of the patient's family in the Intensive Care Unit (ICU). Conclusion: Based on literature conducted in 10 journals originating from the Google Scholar and PubMed data base, it was found that the length of stay in patients can increase the anxiety of the patient's family in the intensive care unit. Suggestion: The researcher's suggestion for future researchers is that the author recommends that future researchers can further expand the writing of literature on similar topics, by comparing more previous research results taken from various other databases.